Initial activation of STAT2 induced by IAV infection is critical for innate antiviral immunity - Li, Xinxin; Liu, Siya; Rai, Kul Raj; Zhou, Wenzhuo; Wang, Song; Chi, Xiaojuan; Guo, Guijie; Chen, Ji-Long; Liu, Shasha (Frontiers in Immunology, 2022)
STAT2 is an important transcription factor activated by interferons (IFNs) upon viral infection and plays a key role in antiviral responses. Interestingly, here we found that phosphorylation of STAT2 could be induced by several viruses at early infection stage, including influenza A virus (IAV), and such initial activation of STAT2 was independent of type I IFNs and JAK kinases. Furthermore, it was observed that the early activation of STAT2 during viral infection was mainly regulated by the RIG-I/MAVS-dependent pathway. Disruption of STAT2 phosphorylation at Tyr690 restrained antiviral response, as silencing STAT2 or blocking STAT2 Y690 phosphorylation suppressed the expression of several interferon-stimulated genes (ISGs), thereby facilitating viral replication. In vitro experiments using overexpression system or kinase inhibitors showed that several kinases including MAPK12 and Syk were involved in regulation of the early phosphorylation of STAT2 triggered by IAV infection. Moreover, when MAPK12 kinase was inhibited, expression of several ISGs was clearly decreased in cells infected with IAV at the early infection stage. Accordingly, inhibition of MAPK12 accelerated the replication of influenza virus in host. These results provide a better understanding of how initial activation of STAT2 and the early antiviral responses are induced by the viral infection.